Manufatura aditiva robotizada: desenvovimento de faixa adequada de parâmetros de impressão 3D para os polímeros PLA e PCL, e para blendas PLA/PCL - Pulquerio, Eduardo Costa (2024)
Additive manufacturing (AM) is a disruptive technology with enormous potential to replace traditional manufacturing methods. There is an optimistic perspective to increase the use of AM because diverse applications were developed, and so many ongoing projects are active. The AM technology based in extrusion, that uses prefabricated polymeric filaments, is known as FFF (Fused Filament Fabrication). By coupling a screw extruder to the printing system, the materials are fed simultaneously with the printing, so the technique is known as FGF (Fused Granular Fabrication). Both techniques have slow manufacturing speed, in comparison to injection molding, for example, that limits their use for mass production. To overcome that disadvantage, a single-screw extruder was coupled to an anthropomorphic robotic arm, configurating the Robotic Additive Manufacturing (RAM), suitable for complex and large-sized 3D objects cases. PLA is a material widely used in AM, therefore, it was evaluated its behavior in the 3D printing system used. The PCL biopolymer was selected to promote a reduction in the elastic modulus and in the extrusion temperature of the PLA. Extruding PLA at a lower temperature can be useful when working with composites, for example in PLA/PCL reinforced with vegetable natural fibers. The materials were thermally characterized by DSC (Differential Scanning Calorimetry) and thermo-mechanically evaluated by DMA (Dynamic-Mechanical Analysis). The most important process parameters were set by a suitable experimental campaign, ensuring a regular geometry of the deposited layer. One-layer 200mm long deposited tracks samples was obtained by the combination of process parameters. After the dimensional measurement, a multiple regression analysis was performed to describe the relationship between the process parameters and the geometry of the layer. The obtained mathematical models were used to set up suitable combination of process parameters for slicing and then printing 3D parts. The printed parts were used in thermo-mechanical evaluations in DMA (Dynamic-Mechanical Analysis). A large-sized 3D object was also printed as study case.